The prognostic value of total T3 after acute cerebral infarction is age-dependent: a retrospective study on 768 patients - Lei-Qing Li; Xiao-Yan Xu; Wen-Yu Li; Xing-Yue Hu; Wen Lv (BMC Neurology, 2019)
Abstract Background Serum triiodothyronine (T3) concentration was reported to be associated with the prognosis after acute ischemic stroke. The aim of this study was to evaluate the effect of age on the prognostic value of thyroid-related hormones after an acute ischemic stroke. Methods This was a retrospective study involving the review of 1072 ischemic stroke patients who had been consecutively admitted to the hospital within 72 h of symptom onset. Total triiodothyronine (T3), total thyroxine (T4), free T3, free T4, and thyroid-stimulating hormone (TSH) were assessed to determine their values for predicting functional outcome at the first follow-up clinic visits, which usually occurred 2 to 4 weeks after discharge from the hospital. Results A total of 768 patients were finally included in the study and divided into two age groups: a younger group (age < 65 years) and an older group (age ≥ 65 years). On univariate analysis, four factors—lower total T3, free T3 concentrations, higher scores on the National Institute of Health Stroke Scale (NIHSS) and the presence of atrial fibrillation—were associated with poor functional outcomes in both groups. In addition, older age, female gender, higher free T4, and lower TSH levels were also associated with poor function in the older group. On multiple logistic regression analysis, higher NIHSS scores (odds ratio [OR] =1.95; 95% confidence interval [CI], 1.66–2.30; P ≤ .001) and lower total T3 concentrations (OR = 0.06; 95% CI, 0.01–0.68; P = .024) remained independently associated with poor functional outcome in the older group. However, the independent association with poor function of lower total T3 was not confirmed in the younger group. Conclusions The prognostic value of low total T3 is age-associated and more meaningful in an older population.